2012
DOI: 10.1016/j.worlddev.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and Moneylender Interest Rate: Evidence from Bangladesh

Abstract: The linkage between the formal and informal credit markets has long been of great interest to development economists. This paper addresses one important aspect of the linkage by empirically investigating the impact of the microfinance program expansion on the moneylender interest rates in Bangladesh, and finds that moneylender interest rates increase with microfinance program expansion. MFI program expansion increases moneylender interest rates in the villages in which more loans are invested in productive eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 24 publications
(21 reference statements)
2
64
0
2
Order By: Relevance
“…at very high interest rates. The moneylender's interest rate varies considerably with a mean of 103.3% with minimum 10% and maximum 240% (Mallick, 2009). The highest percentage of soybean (38.9%) and groundnut farmers (25.9%) expressed this as a major problem (Table 1).…”
Section: Lack Of Cash and Access To Financial Institutionsmentioning
confidence: 99%
“…at very high interest rates. The moneylender's interest rate varies considerably with a mean of 103.3% with minimum 10% and maximum 240% (Mallick, 2009). The highest percentage of soybean (38.9%) and groundnut farmers (25.9%) expressed this as a major problem (Table 1).…”
Section: Lack Of Cash and Access To Financial Institutionsmentioning
confidence: 99%
“…The particular analysis of the impact of macroeconomic factors on the interest rate policy of the MFIs was performed by e.g. Ahlin et al (2011), Mallick (2012 or Roberts (2013). However, their research used different proxy variables or focused on a specific sub-group (only the selected macroeconomic variable, state, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rabobank participates through its different departments in international platforms and partnerships concerning the challenge of economic development in developing countries. Mallick (2009) found that moneylender interest rates go up with the percentage of households borrowing from Micro Financial Institutes (MFIs). Productive investment of loan lowers moneylender interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%